A unified analysis of hybrid ARQ protocol in frequency-hop spread-spectrum systems subject to frequency-selective fading and interference - Daraiseh, A.-G.A.; Baum, C.W. (IEEE transactions on vehicular technology, 1999)
This paper presents an exact analysis of the type-I hybrid automatic repeat request (ARQ) protocol for a frequency-hop (FH) communication system that uses symbol interleaving, multiple codewords per packet, and multiple symbols per dwell interval. The analysis relies on exact formulas for the probabilities of decoder error and failure with an arbitrary number of different conditional symbol error and erasure probabilities. We specialize our analysis to two channel models. The first channel exhibits frequency-selective fading, and the second exhibits frequency-selective interference. The results show that the interrelationships between system and channel parameters are complex and not always intuitive. Numerical results show that: (1) depending on the channel parameters, frequency-selective channel phenomena can result in either an improvement or degradation in system performance compared with an equivalent nonselective channel and (2) in a fading channel, increasing the number of symbols per dwell interval can result in a significant improvement in reliability at only a modest reduction in throughput.